Comparison of Cytotoxicity Between Calcium Silicate and Epoxy Resin-Based Sealerin Root Canal Treatment (Systematic Review) - Hana Zakiyyah Suarsyaf; Rinda Yulianti; Billy Sujatmiko (Dentistry Study Program, Faculty of Medicine Universitas Sriwijaya, 2025)
Introduction: Epoxy resin-based sealer is the gold standard sealer because of its good physical properties. However, epoxy resin sealer has the potential for cytotoxicity which can inhibit the healing process of periapical tissue. Calcium silicate-based sealer is an alternative sealer because of its more biocompatible properties. Methods: The study used PubMed, Google Scholar, and Science Direct databases from 2019 to 2024. The journals used were by the inclusion and exclusion criteria, then bias analysis was carried out and summarized to determine the cytotoxicity of calcium silicate and epoxy resin-based sealer. Results: This study successfully synthesized 19 in vitro journals with low bias results in 16 journals and 3 journals with moderate bias. In general, calcium silicate-based sealers have lower cytotoxicity than epoxy resin-based sealers with the explanation that the composition, conditions, and exposure time of the material play an important role in the biological properties of the sealer. Conclusion: Calcium silicate-based sealers exhibit lower cytotoxicity than epoxy resin-based sealers.